Asian affinities and continental radiation of the four founding Native American mitochondrial DNAs - TORRONI, ANTONIO; SCHURR TG; CABELL MF; BROWN MD; NEEL JV; LARSEN M; SMITH DG; VULLO CM; WALLACE DC (1993)
The mtDNA variation of 321 individuals from 17 Native American populations was examined by high-resolution restriction endonuclease analysis. All mtDNAs were amplified from a variety of sources by using PCR. The mtDNA of a subset of 38 of these individuals was also analyzed by D-loop sequencing. The resulting data were combined with previous mtDNA data from five other Native American tribes, as well as with data from a variety of Asian populations, and were used to deduce the phylogenetic relationships between mtDNAs and to estimate sequence divergences. This analysis revealed the presence of four haplotype groups (haplogroups A, B, C, and D) in the Amerind, but only one haplogroup (A) in the Na-Dene, and confirmed the independent origins of the Amerinds and the Na-Dene. Further, each haplogroup appeared to have been founded by a single mtDNA haplotype, a result which is consistent with a hypothesized founder effect. Most of the variation within haplogroups was tribal specific, that is, it occurred as tribal private polymorphisms. These observations suggest that the process of tribalization began early in the history of the Amerinds, with relatively little intertribal genetic exchange occurring subsequently. The sequencing of 341 nucleotides in the mtDNA D-loop revealed that the D-loop sequence variation correlated strongly with the four haplogroups defined by restriction analysis, and it indicated that the D-loop variation, like the haplotype variation, arose predominantly after the migration of the ancestral Amerinds across the Bering land bridge.